O direito de acesso à Internet - Leandrin, Fernando Henrique Anadão (2019)
This dissertation has its focal point the study of the right to access the Internet and in which manner this right is affirmed and concretized under the Brazilian law system, mostly because of the importance if the Internet as Technology of Information and Communication that revolutionized the world since its creation. In a reflexive way we will analyze relevant questions on the subject and on the present moment, starting with a broad and comprehensive approach, in a way to contextualize the topic treated in Brazilian Society, dealing with historical aspects and social transformation put forward by the Internet in Brazil and over the world, to initially treat of what digital inclusion is about. After depicting this reality, we will move forward to analyze the focal points of the subject-matter under the aspects of the Brazilian positive law, targeting the study to constitutional, infraconstitutional and human rights aspects. In this passage are still considered focal points of discussion themes related to the right of access to the Internet, such as its universalization, mercantile practices experienced in Brazil and over the world, as well as the themes of neutrality of networks also in this comparative context. Once the normative aspect f this study is surpassed, the theme is put in ways to demonstrate and analyze which are the ways of implementing the right to the access of the Internet, opportunity where will be explored and critically analyzed the operation of the public Power and civil Society on the achievement of public policies. Conclusively, through the evaluation of Brazilian constitutional amendments and law-making propositions about the theme of access to the Internet, analytical and critical judgement will be made regarding the selected propositions to cope with the theme of this work